NSQIP as a Predictor of Length of Stay in Patients Undergoing Free Flap Reconstruction. Issue 1 (January 2017) - Riley, Charles A.; Barton, Blair M.; Lawlor, Claire M.; Cai, David Z.; Riley, Phoebe E.; McCoul, Edward D.; Hasney, Christian P.; Moore, Brian A.
Objective: The National Surgical Quality Improvement Program (NSQIP) calculator was created to improve outcomes and guide cost-effective care in surgery. Patients with head and neck cancer (HNC) undergo ablative and free flap reconstructive surgery with prolonged postoperative courses. Methods: A case series with chart review was performed on 50 consecutive patients with HNC undergoing ablative and reconstructive free flap surgery from October 2014 to March 2016 at a tertiary care center. Comorbidities and intraoperative and postoperative variables were collected. Predicted length of stay was tabulated with the NSQIP calculator. Results: Thirty-five patients (70%) were male. The mean (SD) age was 67.2 (13.4) years. The mean (SD) length of stay (LOS) was 13.5 (10.3) days. The mean (SD) NSQIP-predicted LOS was 10.3 (2.2) days ( P = .027). Discussion: The NSQIP calculator may be an inadequate predictor for LOS in patients with HNC undergoing free flap surgery. Additional study is necessary to determine the accuracy of this tool in this patient population. Implications for Practice: Head and neck surgeons performing free flap reconstructive surgery following tumor ablation may find that the NSQIP risk calculator underestimates the LOS in this population.